Predictors of Adverse Clinical Outcomes after Endovascular Thrombectomy in Acute Ischemic Stroke - T. R. Vildanov; V. V. Plechev; M. S. Zagidulina; L. G. Chudnovets; E. M. Kolchina; I. M. Karamova; D. V. Plecheva; G. L. Chudnovets (Креативная хирургия и онкология, 2023)
Introduction. Stroke is recognized as one of the most significant global socio-economic issues. Endovascular interventions, including mechanical thrombectomy of cerebral arteries, have been increasingly performed during the past decade to restore impaired cerebral blood flow in the first hours from the onset of the disease. However, it has been observed that the technical success of the procedure does not always imply an improvement in the clinical condition of a patient.Materials and methods. The study retrospectively analyzes the outcomes of interventions in 86 acute ischemic stroke patients in order to identify factors that can exert an adverse effect on the first hours of the disease and potentially worsen the results of reperfusion therapy. The study involves patients aged 35–85 years (mean age 66.82±1.52 years), predominantly males (57 males versus 29 females). 42 patients (49%) suffered atrial fibrillation, of which 28 (66.7%) had permanent, 11 (26.2%) — paroxysmal, 3 — persistent atrial fibrillation (7.1%), and 27 (31.4%) suffered diabetes mellitus.Results and discussion. Based on the study, factors affecting outcome and one-year long-term results were identified. The predictors included severity of neurological deficit according to Rankin and NIH Stroke scales, time between symptom onset and reperfusion, TICI thrombectomy score, age, diabetes mellitus, and haemorrhagic transformation after thrombectomy.Conclusion. In order to ensure better outcomes, medical specialists should develop an efficient patient routing, pay special attention to the initial severity of neurological deficit, time from the onset of the disease, age of patients, concomitant diabetes mellitus, development of hemorrhagic transformation after endovascular thrombectomy, and, which is particularly important, to the combination of adverse factors.